Expanding the repertoire of gene tools for precise manipulation of the Clostridium difficile genome: allelic exchange using pyrE alleles - Ng, Yen K.; Ehsaan, Muhammad; Philip, Sheryl; Collery, Mark M.; Janoir, Clare; Collignon, Anne; Cartman, Stephen T.; Minton, Nigel P. (Public Library of Science, 2013)
Sophisticated genetic tools to modify essential biological processes at the molecular level are pivotal in elucidating the molecular pathogenesis of Clostridium difficile, a major cause of healthcare associated disease. Here we have developed an efficient procedure for making precise alterations to the C. difficile genome by pyrE-based allelic exchange. The robustness and reliability of the method was demonstrated through the creation of in-frame deletions in three genes (spo0A, cwp84, and mtlD) in the non-epidemic strain 630Δerm and two genes (spo0A and cwp84) in the epidemic PCR Ribotype 027 strain, R20291. The system is reliant on the initial creation of a pyrE deletion mutant, using Allele Coupled Exchange (ACE), that is auxotrophic for uracil and resistant to fluoroorotic acid (FOA). This enables the subsequent modification of target genes by allelic exchange using a heterologous pyrE allele from Clostridium sporogenes as a counter-/negative-selection marker in the presence of FOA. Following modification of the target gene, the strain created is rapidly returned to uracil prototrophy using ACE, allowing mutant phenotypes to be characterised in a PyrE proficient background. Crucially, wild-type copies of the inactivated gene may be introduced into the genome using ACE concomitant with correction of the pyrE allele. This allows complementation studies to be undertaken at an appropriate gene dosage, as opposed to the use of multicopy autonomous plasmids. The rapidity of the ‘correction’ method (5–7 days) makes pyrE− strains attractive hosts for mutagenesis studies.